The Pengaruh Profitabilitas, Leverage, Komisaris Independen, Ukuran Perusahaan dan Capital Intensity Terhadap Penghindaran Pajak - Hidayatul Aini; Andi Kartika (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
Taxes are very important because taxes make a large contribution to state revenue. This study aims to analyze the effect of profitability, leverage, independent commissioners, firm size and capital intensity of tax avoidance. The sample of this research is manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2020 so that in this study 395 data were used. Descriptive statistical test and multiple regression test with SPSS 25 were used to analyze the data. This study shows that the independent profitability variable has a significant positive effect on tax avoidance. On the other hand, leverage, independent commissioners, firm size and capital intensity have no effect on tax avoidance.